Influencia del clima laboral en el rendimiento de los trabajadores de la municipalidad distrital de guadalupe, provincia de pacasmayo, durante el período agosto a diciembre 2013. - Suarez Ramirez, Karem Marilyn (2014)
He present thesis has as intention analyze the personalized individualized work and the crisis of institutional identity, which are the social factors that produce the deficient labor climate in the performance of the workers of the district municipality of Guadalupe, which they influence the labor performance of the own workers and of the municipal strengthening August to December, 2013. The Municipality district of Guadeloupe located in Guadalupe's district; Guadeloupe is placed in the department of The Freedom, to the North West of this one department; located in Pacasmayo Province in the same center of the valley of the river Jequetepeque. The methodology that developed in the present work of investigation went on the basis of "fieldwork", that is to say, to the procedures executed in the place of study the Municipality district of Guadalupe. The study focuses on the work personalized individualized work where it takes form of the inadequate interpersonal relations of the workers of Guadalupe's Municipality and the institutional identity related to the disinterest of the capture of conscience of the internal problematic that happens between the own workers and of his commitment, there affect in the deficient participation of activities for the contributions or offers of improvement organizational that are realized in the Municipality district of Guadalupe.